Identifikasi Naskah dan Telaah Aspek Tekstologis Manuskrip Mushaf Al-Qur’an Syekh Musthofa Lasem - Ulfah, Maria (Al-Qudwah, 2024)
This study aims to investigate the physical attributes and textual features of the Qur’anic manuscript attributed to Shaykh Musthofa, which is housed at the Museum Islam Nusantara in Lasem, Rembang Regency, Central Java. The investigation is driven by the importance of Qur’anic manuscripts as historical evidence documenting the dissemination of Islam throughout the Malay–Indonesian region, as well as their role as written heritage that reflects the cultural and intellectual richness of Indonesian Muslim communities. The study focuses on the script style (rasm), the classification of Makki and Madani surahs, the naming of surahs, the number of verses in each surah, and the presence of waqf marks. The research employs a qualitative method with a descriptive-analytical approach applied to a single manuscript and utilizes a critical edition framework consistent with philological research on religious texts. The results indicate that Qur’anic writing traditions in the archipelago had achieved considerable advancement by the nineteenth century, as evidenced by the diverse and detailed application of waqf and tajwīd signs in the Shaykh Musthofa manuscript. This manuscript demonstrates certain inconsistencies in the use of waqf marks, adheres predominantly to Uthmani script conventions with notable exceptions concerning ḥadhf al-ḥurūf and mā fīhi qirā’atan wa kutiba ‘alā iḥdāhumā, and exhibits variations in verse counts, Makki–Madani classifications, and surah titles relative to the Indonesian Standard Mushaf. These findings imply that the manuscript tradition in the archipelago not only facilitates the transmission of the sacred text but also embodies local innovation in adapting and contextualizing the Qur’an within the cultural and aesthetic paradigms of Indonesian Muslim society.Abstrak: Penelitian ini bertujuan untuk menginvestigasi karakteristik fisik dan aspek tekstologi manuskrip mushaf Al-Qur’an Syekh Musthofa yang tersimpan di Museum Islam Nusantara, Lasem, Kabupaten Rembang, Jawa Tengah. Kajian ini dilatarbelakangi oleh pentingnya manuskrip mushaf Al-Qur’an sebagai jejak penyebaran Islam di Nusantara serta sebagai warisan tulis yang memperlihatkan kekayaan budaya dan intelektual masyarakat Muslim Indonesia. Fokus penelitian diarahkan pada bentuk rasm, pengkategorian makki–madani, penamaan surat, jumlah ayat dalam setiap surat, serta keberadaan tanda waqaf. Metode yang digunakan adalah metode kualitatif dengan teknik deskriptif-analitis terhadap naskah tunggal dengan pendekatan edisi kritis sebagaimana diterapkan dalam studi filologi manuskrip keagamaan. Hasil penelitian menunjukkan bahwa kreativitas penulisan Al-Qur’an di Nusantara telah berkembang pesat sejak abad ke-19, dibuktikan dengan variasi dan kelengkapan tanda waqaf serta tajwid dalam manuskrip Syekh Musthofa. Manuskrip ini memiliki inkonsistensi dalam penulisan tanda waqaf, mengikuti rasm Utsmani dengan pengecualian pada aspek ḥadzf al-ḥuruf dan ma fīh qirā’atan wa kutiba ‘alā ihdāhumā, serta menunjukkan perbedaan jumlah ayat, kategori makki–madani, dan penamaan surah dibandingkan Mushaf Standar Indonesia. Temuan ini mengimplikasikan bahwa tradisi penyalinan mushaf di Nusantara tidak hanya merepresentasikan transmisi teks suci, tetapi juga kreativitas lokal dalam mengolah dan menyesuaikan Al-Qur’an dengan konteks budaya dan estetika masyarakat setempat.